2019
DOI: 10.1002/ehf2.12392
|View full text |Cite
|
Sign up to set email alerts
|

Design and rationale of haemodynamic guidance with CardioMEMS in patients with a left ventricular assist device: the HEMO‐VAD pilot study

Abstract: AimsWe aim to study the feasibility and clinical value of pulmonary artery pressure monitoring with the CardioMEMS™ device in order to optimize and guide treatment in patients with a HeartMate 3 left ventricular assist device (LVAD).Methods and resultsIn this single‐centre, prospective pilot study, we will include 10 consecutive patients with New York Heart Association Class IIIb or IV with Interagency Registry for Mechanically Assisted Circulatory Support Classes 2–5 scheduled for implantation of a HeartMate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 31 publications
(54 reference statements)
1
20
0
Order By: Relevance
“…The clinical benefit of a wireless implantable hemodynamic monitoring system (CardioMEMS) in patients with LVADs is being studied in the Intellect2 and HEMO-VAD studies [44,45]. Analysis of patients from the CHAMPION Trial who subsequently received LVADs showed that PA pressures decreased dramatically post-implant in all patients, but the degree of improvement was greater in the treatment group wherein physicians used the hemodynamic information to make management decisions [46].…”
Section: Long-term Managementmentioning
confidence: 99%
“…The clinical benefit of a wireless implantable hemodynamic monitoring system (CardioMEMS) in patients with LVADs is being studied in the Intellect2 and HEMO-VAD studies [44,45]. Analysis of patients from the CHAMPION Trial who subsequently received LVADs showed that PA pressures decreased dramatically post-implant in all patients, but the degree of improvement was greater in the treatment group wherein physicians used the hemodynamic information to make management decisions [46].…”
Section: Long-term Managementmentioning
confidence: 99%
“…Finally, an attempt has been made to test the feasibility of combining remote hemodynamic monitoring in patients on LVAD support in the HEMO-VAD pilot study [18]. This study focussed on hemodynamic optimization, especially with diuretics, based upon PA pressures before surgery (to truly decongest the right ventricle and kidney in order to improve post-operative outcomes) and tests the feasibility of using CardioMEMS in the outpatient clinic phase of LVAD patients for assessment of volume status, arrhythmias and other VAD related complications [18][19][20]. A larger pivotal trial is underway in the U.S. to test the clinical use of CardioMEMS in optimization of LVAD support (INTELLECT2 trial, ClinicalTrials.gov Identifier: NCT03247829).…”
Section: Potential Use Of Hybrid Constructions Of Current Therapies Wmentioning
confidence: 99%
“…Thus far, the clinical implication of ReDS in LVAD patients remains unknown. The CardioMEMS device might have the potential to be utilized in LVAD patients to monitor and adjust device parameters in response to hemodynamic status [63]. This is of course not without considering important limitations.…”
Section: Remote Dielectric Sensing (Reds)mentioning
confidence: 99%